Calcium phosphate nanoparticles as a new generation vaccine adjuvant - Yahua Lin; Xin Wang; Xiaofen Huang; Jun Zhang; Ningshao Xia; Qinjian Zhao (Taylor & Francis Group, 2017)
Introduction: Adjuvants are essential components in vaccine formulations to induce robust immunity against pathogens. The most widely used adjuvants in human vaccines are aluminum salts, that can effectively elicit a T helper type-2 (Th2)-biased humoral immune response for producing a high antibody titer but with a limited cellular immune response. Biocompatible calcium phosphate nanoparticles (CaP-NPs) with tunable characteristics have potentials to function as adjuvants for inducing more balanced T helper type-1 (Th1) and Th2 immune responses. Areas covered: Here we review the preparation procedures and characteristics of CaP-NPs. The process can be well-controlled and readily scaled up. Antigen loading can take place as encapsulation during the particle formation or as passive adsorption post particle formation. Different modalities of immunogens were tested with CaP-NPs as adjuvants. The possible mechanisms of the CaP-NP-based adjuvants are discussed. Expert commentary: With good adjuvant effects and safety profiles, CaP-NPs have the potentials to be a new generation vaccine adjuvant. A more in-depth understanding of the mechanisms of their adjuvanticity could facilitate the process optimization for making adjuvants with preferred characteristics. Interdisciplinary collaborations are essential for testing the biocompatible CaP-NPs in human vaccines for clinical development and eventually for use in marketed vaccines.